The Frame problem in artificial intelligence : proceedings of the 1987 workshop, April 12-15, 1987, Lawrence, Kansas - Brown, Frank M., 1950- (Morgan Kaufmann Publishers, 1987)
The Frame Problem in Artificial Intelligence.